Nilai Keislaman dalam Cerita Wayang Kulit dengan Lakon Babad Alas Wanamarta di Kabupaten Karanganyar - Pepsi Febriyanti; Rochmat Budi Santoso (Sekolah Tinggi Agama Islam Taruna Surabaya, 2023)
The purpose of this article is to show that wayang kulit is a vehicle for the spread of Islam in the land of Java and to show the Islamic values ​​contained in the story of wayang kulit with the Lakon Babat Alas Wanamarta. The researcher has two problem formulations, why wayang kulit is used as a vehicle for the spread of Islam in Java and what Islamic values ​​are contained in the wayang kulit story with the Lakon Babat Alas Wanamarta. This study used a descriptive qualitative method with data collection techniques through documentation and interviews. Documentation is done by viewing video recordings of wayang performances. Interviews were conducted with the puppeteers who often perform wayang performances. The result of this study is that wayang kulit became a medium for spreading Islam by Sunan Kalijaga. Sunan Kalijaga spread Islam through a cultural approach. Wayang kulit was chosen because at that time wayang kulit was something that was popular. So that the spread of Islam through wayang kulit is easily accepted by the community by being associated with the play in each wayang story. In this Lakon, one of them is the Lakon Babat Alas Wanamarta which contains Islamic values, such as ridho, istiqomah, and tawakal.